Tingkat Kepatuhan Minum Obat Pada Pasien Hipertensi Berdasarkan Sosiodemografi di Salah Satu Puskesmas di Kota Pekanbaru - Husnawati - Husnawati (JURNAL FARMASI DAN MAKANAN, 2023)
Hypertension is a chronic disease that cannot be cured, but can be controlled and requires long-term or even lifelong treatment. Hypertension drugs must be taken regularly to control blood pressure and avoid the risk of complications. An important factor in achieving successful hypertension therapy is adherence. Conversely, non-adherence is one of the main factors causing therapy failure. This study aims to determine the level of medication adherence in hypertensive patients at one of the community health centers in Pekanbaru city. This research is an observational study with a descriptive research design using concurrent data collection techniques. The sampling technique in this study was carried out non-randomly using purposive sampling method. The sample in this study were 105 respondents who met the inclusion criteria. The results showed that most of the respondents were aged 41-60 years (middle adults), female, with junior high school education levels (secondary education) and unemployed employment status. The level of adherence in terms of gender and employment status did not differ much, but based on age and level of education, the older the age and the higher the level of education, the higher the level of adherence